Performance of Separation Processes for Precipitated Calcium Carbonate Produced with an Innovative Method from Steelmaking Slag and Carbon Dioxide - Teir, Sebastian; Auvinen, Toni; Said, Arshe; Kotiranta, Tuukka; Peltola, Heljä (Frontiers in Energy Research, 2016)
In this work, experiments were performed to determine the filterability of calcium carbonate produced with an alternative calcium carbonate production concept. The concept uses steelmaking slag as raw material and has potential to fix CO2 emissions and utilize steelmaking slag, simultaneously. As calcium carbonate is precipitated in a solution containing ammonium chloride, calcium chloride, and ammonia, the product needs to be washed and hence filtered. In this work, different separation processes, including washing, filtering, and drying, were tested on two calcium carbonate slurries produced from steel converter slag and CO2 by a laboratory-scale pilot facility, with the aim of obtaining a solid product with a low chloride content using a minimum amount of washing water. The order of maximum filtration rates achievable of the calcium carbonate slurries was determined by experimental work. The tests included pressure filtration and vacuum filtration and the test series contained altogether 21 different filtration cycles with varying combinations of filtering, washing, and drying steps. The filtered cakes were analyzed by their residual moisture content, chloride content, and conductivity, and the filtrates by their residual solids content, chloride content, and conductivity. Pressure filtration gave a high capacity (400–460 kg/m2h) and a low cake residual moisture content (12–14 wt-%). Vacuum filtration gave slightly higher filtration rates (500–610 kg/m2h at the lowest residual chloride contents of the cakes), but the cake residual moisture also stayed higher (25–26 wt-%). As the vacuum filtration tests used a filter cloth with higher permeability than that of the pressure filtration tests, a slightly higher filtration rate was expected. However, both filtration technologies seem suitable for filtering and washing calcium carbonate prepared with the studied method as a residual chloride content as low as 10 ppm of the filtered solids can be achieved with quite a small amount of washing water and the filtration rate is fast.